#TITLE_ALTERNATIVE# - DIMASPRIA WIDODO (NIM: 15108015); Pembimbing: Dr.Irwan Meilano, ST, M.Sc. ; Heri Andreas, ST,, ELGAR
Exploration activity in Kenali Asam,Jambi is done since the days of the Dutch colonial, which has been submitted to PT.Pertamina. This activity leaves an oil and gas wells and a documentation about its topocentric coordinates. The reference about topocentric coordinate system was not included in the documentation. Today most of the wells are re-measured using GPS. GPS measurements carried out to obtain a position on the land coordinate that currently used is WGS 1984, so most of the wells can be used as a common points for a coordinate transformation. Therefore, it needs datum analysis to obtain the most suitable transformation methods in the area. This study paper was made in order to solve the coordinate problem to make a map with the WGS 1984 system. The methodology used in this paper is to determine eligibility and distribution of common points, transformation using a 2-dimensional and 3-dimensional method including: Helmert, Affine, and Bursa-Wolf, in order to obtain the most suitable methods in the area, defining the reference system of local coordinates for 3-dimensional datum transformation. After all, analyzing the results of the transformation using photogrammetric imagery and Chi-square statistical method. The results of the study, the used of ellipsoid reference is Bessel 1841 with the most suitable method of transformation is Affine. That statement can be proved with a match of the position in photogrammetry, small residual value of x and y, and passed the test of Chi-square statistics.